Apoptosis, Paraptosis and Autophagy: Death and Survival Pathways Associated with Photodynamic Therapy1. (17th July 2018) - Kessel, David
Abstract: The ability of photosensitizing agents to create photodamage at specific subcellular sites has proved useful for characterizing pathway(s) to cell death and for selecting optimal targets for anti‐tumor efficacy. Both apoptosis and autophagy can occur after photodamage directed at mitochondria, lysosomes or the ER, with the balance often a determinant of overall efficacy. A combination of lysosomal + mitochondrial targets is associated with enhanced efficacy. More recently, ER photodamage was found to evoke a mainly unexplored mode of photokilling that involves extensive cytoplasmic vacuole formation but does not represent autophagy. This has been termed "paraptosis" and appears to be a reaction to the appearance of misfolded ER proteins. This report is designed to summarize current knowledge relating to death pathways and update information relating to paraptosis as a PDT response. Abstract : Image of paraptosis showing an extensive series of cytoplasmic vacuoles 16 h after irradiation of OVCAR‐5 cells photosensitized with hypericin.